Peningkatan Kapasitas Usaha Jamu Gendong “Jamu Seger Bu Mur” Melalui Diversifikasi Bentuk Sediaan Dan Perbaikan Kemasan - Kartini, Kartini; Fatimah, Umi; Anggraeni, Maya Harfi; Setiawan, Finna; Nugroho, Eko (Majalah Cendekia Mengabdi, 2023)
Introduction: The herbal medicine business (in Bahasa called as Usaha Jamu Gendong or UJG) "Jamu Seger Bu Mur" is one of the small business engaged in the field of herbal or herbal drinks located around the University of Surabaya campus. This UJG has various obstacles to survive in the midst of changing times and business competition in urban areas. Objectives: This mentoring program is intended to increase the capacity and competitiveness of UJG "Jamu Seger Bu Mur" so that it can continue to run its business, as well as one of the efforts to increase the role of educational institutions in the preservation of Indonesian traditional medicines. Methods: This program was carried out using a mentoring approach model, where mentoring activities were divided into two stages, namely training in making instant herbal medicine (powder form) and assistance in improving product packaging and labels. Results: The results obtained from this program were an increase in the skills of partners to diversify herbal dosage forms, namely instant powder forms. In addition, with improvements to product packaging and labels, partners' confidence in the products they produce has also increased so that the enthusiasm to continue running their business has also increased. Conclusion: The assistance activities carried out have succeeded in encouraging UJG "Jamu Seger Bu Mur" to continue its business in the field of traditional medicine, especially herbal medicine. Keywords: herbal medicine business, instant herbal medicine, product diversification, product packaging, traditional medicine